Epidermal growth factor regulates autophagy activity and endocytosis of yak cumulus cells in a concentration-dependent manner - Ma, Rui; Yu, Sijiu; Cui, Yan; Pan, Yangyang; Wang, Meng; Wang, Libin; Wang, Jinglei; Zhao, Ling; Zhang, Hui (Frontiers in Veterinary Science, 2023)
Autophagy and endocytosis are crucial biological activities in mammalian follicle development and oocyte maturation, which are easily affected by external environmental factors. EGF, as an important component of follicular fluid, regulates the growth and apoptosis of follicular cells. However, its regulatory mechanism of autophagy and endocytosis in mammals, especially in large domestic animals such as plateau yak, remains unclear. This study aimed to investigate the regulatory mechanism of EGF on autophagy and endocytosis in yak cumulus cells. Yak cumulus cells were treated with different concentrations of EGF and appropriate concentrations of EGFR inhibitor gefitinib (10 μmol/L). EGF inhibited autophagy in yak cumulus cells by down-regulating the expression of Atg5, Beclin1, and LC3. The level of autophagy varied with the concentration of ligands, and the inhibition was most significant at 100 ng/mL. Noteworthy, EGF can promote endocytosis by regulating the expression of Cav1 and Cav2, but the EGFR-mediated signaling pathway is not the main way to regulate the expression of these proteins. These results provide a reference for further exploring the effects of growth factors on livestock germ cells and the regulatory role of autophagy-endocytosis crosstalk mechanism in follicle development and oocyte maturation, to improve the fecundity of yaks.